Strategy for improved therapeutic efficiency of curcumin in the treatment of gastric cancer - Jakubek, Milan; Kejík, Zdeněk; Kaplánek, Robert; Hromádka, Róbert; Šandriková, Viera; Sýkora, David; Antonyová, Veronika; Urban, Marian; Dytrych, Petr; Mikula, Ivan; Martásek, Pavel; Král, Vladimír (Biomedicine & pharmacotherapy, 2019)
Gastric cancer is a common oncological disease. Although enormous efforts have been expended, possible therapeutic modalities are still limited. For this reason, new therapeutic approaches and agents are highly requested and intensively developed. One strategy is the application of natural agents, such as curcumin, with proven anticancer effects and low toxicity for patients. Therefore, this review discusses the potential application of curcumin in the therapy of gastric cancer and its potential incorporation in therapeutic regimens. Because one of the largest impediments for widespread curcumin application is its limited bioavailability (caused mainly by its very low water solubility), studied strategies (drug delivery systems and curcumin derivatization) aimed to solve this obstacle are discussed in more detail.
Keywords: biologické modely; výsledek terapie; Models, Biological; Stomach Neoplasms; Animals; Curcumin; kurkumin; Drug Delivery Systems; zvířata; Humans; lékové transportní systémy; Treatment Outcome; lidé; nádory žaludku